Between a rock and a hard place, third space practitioners exercise agency - Behari-Leak, Kasturi; Le Roux, Natalie (Faculty of Education, University of the Free State, 2018)
Academics as well as educational and academic development practitioners often find themselves in an ambiguous space in which personal and professional transformation can take place. Moving constantly between contexts and cultural learning environments at the university, these practitioners inhabit a strange, in-between space between mainstream academic support work, leadership and advocacy and other roles at the periphery. This space known as the third space from which other positions emerge, displaces the histories that constitute it and sets up new structures of authority, practice and discourses which are not always congruent with the university at large. This paper critically reflects on the experiences and insights of academics in a specific professional development course for new academics. Using a critical discourse analysis of in-depth, semi-structured narrative interviews, the authors explore the journey of new academic practitioners as they exercise their agency to carve out a hybrid identity in the third space across institutional boundaries. While resistance and struggle are challenging aspects of third space work, these constitute legitimate processes of identity construction and socialisation through contestation of traditional roles at the university. This paper interrogates the university’s role in creating and sustaining enabling institutional conditions so that academics can work in creative, responsive and relevant ways in a changing higher education landscape.
Keywords: Third space; Professional development; New academics; Agency